A new species of Macbrideola on galls of Rosaceae - Moreno, G.; Seraoui, El-Hacène; Meyer, M.; López-Villalba, Á. (Phytotaxa, 2023)
Macbrideola gallicola is described as a new species to science after studying specimens collected in France and Montenegro, fructifying on galls of Rosaceae. The new species can be distinguished by the loose and flexuous capillitium, the conspicuously, spiny spores, and by its habitat. Macro- and micrographs of the morphological characters are provided.